Probiotics on performance, intestinal morphology and carcass characteristics of broiler chickens raised with lower or higher environmental challenge - Souza, Lilian F. A. de; Araujo, Denise N.; Stefani, Lenita M.; Giometti, Ines C.; Cruz-Polycarpo, Valquiria C. [UNESP]; Polycarpo, Gustavo [UNESP]; Burbarelli, Maria F. (Univ Austral Chile, Fac Ciencias Veterinarias, 2018)
This study aimed to evaluate the effect of probiotics on performance, intestinal morphology and carcass characteristics of broiler chickens housed on lower or higher environmental challenge. Three hundred male Cobb chicks were distributed into four groups in completely randomised design with treatments arranged in a 2 x 2 factorial scheme to evaluate effects of two diets (with or without probiotics) and two environmental conditions (lower or higher challenge), totaling four treatments with five replications with 15 birds per box. Probiotics were added on diets and were composed of Lactobacillus acidophilus, Bacillus subtilis, Bifidobacterium bifidum and Enterococcus faecium. The environment with lower challenge was made up of new wood shavings used as litter, low bird density (8 birds/m(2)) and daily-cleaned bell drinkers. The environment with higher challenge was made up of re-used wood shavings used as litter (after three broods of broilers), bird density of 16 birds/m(2) with bell drinkers cleaned every two days. No significant interaction between diet and environmental challenge was found for any of the variables evaluated. Performance, slaughterhouse variables and chemical carcass composition were not affected by the use of probiotics. Chicks receiving diets without probiotics had lower intestinal crypt depth (267.1 vs. 316.6 mu m, P=0.0068). Birds raised in the environment with higher challenge decreased feed intake (4,660 vs 5,020 g, P=0.0422), weight gain (2,610 vs 2,810 g, P=0.0054), drumstick and thigh yield (21.98 vs 24.14 %, P=0.0354), and increased crypt depth (325.2 vs 258.5 mu m P=0.0009). In conclusion, the probiotic does not promote satisfactory improvements, regardless of the environmental challenge.
Keywords: additives; intestinal health; poultry; sanitary challenge